Friends...with consequences - Bennett, Jules (Bennett, Jules. Business and babies, 2023)
"CEO Zane Westbrook is Nora Monroe's boss, her best friend's brother...and after one unexpected night, the father of her baby! Moving in with Zane so he can take care of her is one thing-sharing his bed (again!) is quite another. Suddenly, Nora's doing both, and the nights sizzle. But can their deepening bond survive Zane's brother discovering their betrayal?"--